2012
DOI: 10.1007/s11661-012-1144-2
|View full text |Cite
|
Sign up to set email alerts
|

Full Densification of Molybdenum Powders Using Spark Plasma Sintering

Abstract: Pure molybdenum powder was sintered using Spark Plasma Sintering under various temperatures, and holding times, under a pressure of 77 MPa and a heating rate at 700°C/min. After sintering, a carbide layer was observed at the surface. The carbide layer thickness, the relative density of the sample as well as the microhardness and the grain size of Mo were measured. The carbide thickness depends on time and temperature and it was found that the carbide layer grows in a parabolic manner, with the activation energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The advantage of HIP is the reduction of production times and the variation of properties in the solid, obtaining almost finished parts and parts with complex shapes or small sizes due to its isostatic processing. It is noteworthy in this instance that the model used will be validated over similar powder forming processes where the application of temperature and pressure is performed simultaneously [26][27][28].…”
Section: Hot Isostatic Pressingmentioning
confidence: 99%
“…The advantage of HIP is the reduction of production times and the variation of properties in the solid, obtaining almost finished parts and parts with complex shapes or small sizes due to its isostatic processing. It is noteworthy in this instance that the model used will be validated over similar powder forming processes where the application of temperature and pressure is performed simultaneously [26][27][28].…”
Section: Hot Isostatic Pressingmentioning
confidence: 99%
“…The disadvantages are: (i) it is very difficult in achieving full densification and (ii) very difficult to assembly with AlN without any additives using standard solution [9]. Preliminary results in the densification of pure Molybdenum shows that a full densification can be obtained using a new sintering technique such as Spark Plasma Sintering [10]. We suggest to use the same sintering technique to realize both molybdenum powder sintering, and Mo / AlN layers bonding simultaneously.…”
Section: Molybdenum / Alnmentioning
confidence: 99%
“…At the end of each experiment, the samples were crosssectioned, mounted in a hot mounting resin (Presi Phenolic resin) and then prepared metallographically (mechanical a. Molybdenum sintering parameters reported in [10] grinding and polishing down to 0,05 µm silica slurry). The samples were examined using optical and scanning electron microscopy (SEM).…”
Section: B Samples Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…SPS has been widely used because of its ability to heat up the material very quickly, providing a powerful tool to retain the original nanostructure [16e19]. For industrial purpose, it has been used for ceramics applications and refractory materials whereas only few studies were dedicated to metallic materials [20,21]. Ji et al [17,22] demonstrated that SPS can be used to retain the nanostructure of ODS intermetallic alloys.…”
Section: Introductionmentioning
confidence: 99%